Intentional injuries in the Eastern Mediterranean region, 1990-2015: findings from the Global Burden of Disease 2015 study - Moradi-Lakeh, Maziar; Jonas, Jost B.; Mohammed, Shafiu (International journal of public health, 2017)
We used GBD 2015 findings to measure the burden of intentional injuries in the Eastern Mediterranean Region (EMR) between 1990 and 2015.